Feasibility analysis of the cow manure (Bos taurus) biodigester as a renewable energy source in the Ahuaycha district, 2023 - Ccora Repuello, Braulio (2023)
The objective of the research was to analyze the feasibility of a cattle manure (Bos taurus) biodigester as a renewable energy source in the district of Ahuaycha. The methodology was applied research, and direct observation was used to determine the manure content and size of the biodigester. The results showed the amount of manure produced by the cows per day, month and year, 1 cow (Bos taurus) produces 4 kg of manure per day, to find the amount of the 12 cows (sample) mathematical operations were performed, which gave a result of 48 kg/day of manure. The biodigester will be tubular and will consist of 4 main parts: the inlet vessel, which serves to introduce the organic matter mixture into the reactor; the biol outlet, which serves to discharge waste from the reactor; and the biogas outlet, which serves to take advantage of the gas accumulated in the biodigester. Therefore, it is concluded that the implementation of the biodigester is viable, because it performs better than domestic gas due to its high concentration of methane, it is also economical and a tool to promote changes in the management of organic waste, thus promoting a more sustainable development in the district of Ahuaycha.